Control of electrolyte intrusion in carbon-free silver gas diffusion electrodes for electrochemical CO2 reduction - Inga Dorner; Jens Osiewacz; Philipp Röse; Barbara Ellendorff; Maximilian Röhe; Thomas Turek; Ulrike Krewer (Journal of CO2 Utilization)
Achieving high conversion rates in electrochemical CO2 reduction requires gas diffusion electrodes to ensure sufficient CO2 availability at the electrode surface. Carbon-free Ag electrodes offer superior stability compared to carbon-based ones but are challenged by complex electrolyte intrusion and distribution. This study combines experimental variations in electrode design and operating parameters with modeling to identify key factors for high Faradaic efficiency towards CO and high current densities. Results emphasize the importance of an optimal gas/liquid interface. Increasing gas-side overpressure from 60 to 100 mbar doubled the Faradaic efficiency for CO from 20 % to 42 % at 200 mA cm−2 due to higher local CO2 concentrations in electrolyte-flooded regions. Thin electrodes of 200 µm outperformed thicker ones up to 390 µm, achieving higher efficiencies by enhancing CO2 and electrolyte transport, which lowered local pH levels. Optimizing PTFE content further improved performance; reducing PTFE from 2 to 1 wt% increased Faradaic efficiency by 20 % at 200 mA cm−2 by balancing hydrophobicity and active surface exposure. These insights into the relationship between electrode properties, operating conditions, and gas-liquid distribution advance the design of gas diffusion electrodes for competitive CO2 reduction applications.